2022
DOI: 10.1002/ese3.1130
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring of renewable energy systems by IoT‐aided SCADA system

Abstract: With the rapid increase of renewable energy generation worldwide, real‐time information has become essential to manage such assets, especially for systems installed offshore and in remote areas. To date, there is no cost‐effective condition monitoring technique that can assess the state of renewable energy sources in real‐time and provide suitable asset management decisions to optimize the utilization of such valuable assets and avoid any full or partial blackout due to unexpected faults. Based on the Internet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(8 citation statements)
references
References 47 publications
1
7
0
Order By: Relevance
“…For example, Tran Thanh Son and coauthors showed a simple IoT-SCADA that relies for its operation on wireless power sensors using a set of small rooftop photovoltaic arrays in Vietnam as test site [21]. In [22], Quays and coauthors presented an IoT-SCADA for a mixed-generation small system composed of photovoltaic, wind, and batteries, where wireless sensors are used for real-time monitoring of current and voltage. Again, Aghenta and Iqbal in [23] examined in detail the basic structural elements of a generic IoT-SCADA in terms of usable IoT protocols, proposing and testing possible photovoltaic system hardware configurations designed for small PV applications.…”
Section: Literature Reviewmentioning
confidence: 99%
“…For example, Tran Thanh Son and coauthors showed a simple IoT-SCADA that relies for its operation on wireless power sensors using a set of small rooftop photovoltaic arrays in Vietnam as test site [21]. In [22], Quays and coauthors presented an IoT-SCADA for a mixed-generation small system composed of photovoltaic, wind, and batteries, where wireless sensors are used for real-time monitoring of current and voltage. Again, Aghenta and Iqbal in [23] examined in detail the basic structural elements of a generic IoT-SCADA in terms of usable IoT protocols, proposing and testing possible photovoltaic system hardware configurations designed for small PV applications.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The operator can see the live data and take the required action. A SCADA system was implemented to monitor the electrical parameters (power, voltage, current) of a hybrid system comprising wind, PV, and energy storage systems [4]. The real-time data is monitored using the ThingsSpeak platform.…”
Section: Literature Reviewmentioning
confidence: 99%
“…However, a bigger number of remote units increase the cost of a communication unit inside the infrastructure medium. To reduce the number of remote units, operations are carried out using allocation of renewable energy sources in the path between two SCADA networks [20], and as a result, the IoT-based operation is flexible by reducing the cost of installations. On the other hand, the IoT operation is carried out using low security open source tool, and this type of SCADA operation requires modernization of the entire network.…”
Section: Literature Surveymentioning
confidence: 99%